Sex differences in learned fear expression and extinction involve altered gamma oscillations in medial prefrontal cortex - Fenton, G.E.; Halliday, D.M.; Mason, Rob; Bredy, Timothy W.; Stevenson, Carl W. (Elsevier, 2016)
Sex differences in learned fear expression and extinction involve the medial prefrontal cortex (mPFC). We recently demonstrated that enhanced learned fear expression during auditory fear extinction and its recall is linked to persistent theta activation in the prelimbic (PL) but not infralimbic (IL) cortex of female rats. Emerging evidence indicates that gamma oscillations in mPFC are also implicated in the expression and extinction of learned fear. Therefore we re-examined our in vivo electrophysiology data and found that females showed persistent PL gamma activation during extinction and a failure of IL gamma activation during extinction recall. Altered prefrontal gamma oscillations thus accompany sex differences in learned fear expression and its extinction. These findings are relevant for understanding the neural basis of post-traumatic stress disorder, which is more prevalent in women and involves impaired extinction and mPFC dysfunction.